Bishop, Special Crimes : Blood Sins - Book 11 - Hooper, Kay (New York : Bantam Books, 2009)
All clues to the recent rash of murders point to the enigmatic Church of the Everlasting Sin and its charismatic leader, the Reverend Adam Deacon Samuel. But getting to the man known as 'Father' will be no easy task, for he is insulated within his flock of loyal minions--closely guarded by those who would gladly give their lives for his. Now, with the support of Haven, the civilian agency Bishop helped launch, the elite FBI Special Crimes Unit must go deep into the fold of a puppetmaster whose power reigns over more than they could ever have imagined.
"A Bishop/Special Crimes Unit novel"--Jacket.
Keywords: Bishop, Noah (Fictitious character) -- Fiction; Government investigators -- Fiction; Suspense fiction; Mystery fiction